2015
DOI: 10.1002/app.42579
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a PPV‐fluorene derivative: Applications in luminescent devices

Abstract: Synthesis of a polyfluorene/poly(p-phenylene vinylene) derivative, the Poly [(9,9 0 -di-hexylfluorenediylvinylene-alt-1,4-phenylenevinylene)-co-((9,9 0 -(3-t-butylpropanoate) fluorene-1,4-phenylene)] (LaPPS 42) was performed following Wittig and Suzuki routes. Polyfluorenes and derivatives have been used in electroluminescent devices, and the synthesis described here has the advantage in pave the way to get distinct structures having different emission spectra. An extensive study of its electrochemical, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Monomers M‐1, M‐4, and M‐5 were prepared following procedures outlined in Data S1. The synthesis of PFeBT, PFeBSe, PFeTBTT, and PFeTBSeT (Scheme 1) was performed according to the procedure reported in the literature 26–28 . In a typical experimental procedure, a 25 mL flask was filled with (0.31 mmol) of the respective dibromo‐monomer (M‐2, M‐3, M‐4, or M‐5), (0.31 mmol) of 2‐(4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolan‐2‐yl)‐9,9‐bis(3‐(tert‐butyl propanoate))fluorene (M‐1), 8 mg of Pd(Ph 3 P) 4 , and (3.7 mmol) of potassium carbonate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monomers M‐1, M‐4, and M‐5 were prepared following procedures outlined in Data S1. The synthesis of PFeBT, PFeBSe, PFeTBTT, and PFeTBSeT (Scheme 1) was performed according to the procedure reported in the literature 26–28 . In a typical experimental procedure, a 25 mL flask was filled with (0.31 mmol) of the respective dibromo‐monomer (M‐2, M‐3, M‐4, or M‐5), (0.31 mmol) of 2‐(4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolan‐2‐yl)‐9,9‐bis(3‐(tert‐butyl propanoate))fluorene (M‐1), 8 mg of Pd(Ph 3 P) 4 , and (3.7 mmol) of potassium carbonate.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of PFeBT, PFeBSe, PFeTBTT, and PFeTBSeT (Scheme 1) was performed according to the procedure reported in the literature. [26][27][28] In a typical experimental procedure, a 25 mL flask was filled with (0.31 mmol) of the respective dibromo-monomer (M-2, M-3, M-4, or M-5), (0.31 mmol) of 2-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9,9-bis (3-(tert-butyl propanoate))fluorene (M-1), 8 mg of Pd(Ph 3 P) 4 , and (3.7 mmol) of potassium carbonate. A mixture of water: toluene (3:1) was then added to the flask, followed by bubbling Ar into the system for 20 min.…”
Section: Copolymer Synthesismentioning
confidence: 99%
“…It has been reported that carbonyl and amine functional groups are effective in mixtures of polyurethane and polyaniline [18]. The IR spectra of PU/PANI blends are shown in Fig.…”
Section: Morphology and Structurementioning
confidence: 96%
“…Besides, coupling aromatic substitutes at the 2,7-position using Suzuki cross-coupling reactions, for instance, allows the control of its optical and electronic properties . Furthermore, applications in three-dimensional optical data storage, optical limiting, two-photon polymerization fabrication–due to a high two-photon absorption –light-emitting electrochemical cells (LECs), as a hole transport layer in perovskite solar cells, and, recently, in optical amplifiers that can be used in visible-light communication, have been reported.…”
Section: Introductionmentioning
confidence: 99%